A Pilot Prospective Comparative Trial of High-Intensity Focused Ultrasound versus Cryolipolysis for Flank Subcutaneous Adipose Tissue and Review of the Literature. (September 2013) - Friedmann, Daniel P.; Mahoney, Leysin; Fabi, Sabrina; Goldman, Mitchel P.
Introduction: Multiple treatment modalities exist for noninvasive body sculpting and reduction of focal adipose deposits, including high-intensity focused ultrasound (HIFU) and cryolipolysis. The focus of this study was to compare the efficacy of HIFU and cryolipolysis in the reduction of localized subcutaneous adipose tissue in the flank region. Materials and Methods: Eight female patients with subcutaneous adipose tissue localized to the bilateral flanks were randomized to a single treatment with either HIFU or cryolipolysis to each flank. Weight and widest-point waist circumference were recorded at baseline and at 4 monthly follow-up visits, with no significant change in weight over the study period. Two blinded investigators graded baseline and 4-month follow-up photographs for improvement using a 5-point global aesthetic improvement scale. Results and Discussion: Although both HIFU and cryolipolysis led to modest reductions in localized flank subcutaneous adipose tissue, there was a trend toward greater improvement in the HIFU treatment group.